Hybrid 2D Phosphorene‐Black Carbon Material for Dye‐Sensitized Solar Cells as Counterelectrode - Sarah Derbali; Ghassane Tiouitchi; Omar Mounkachi; Abdelmajid Almaggoussi; Omar Moudam (Advanced Energy & Sustainability Research)
Since the discovery of graphene in 2004, 2D materials have been the subject of extensive research, in particular, 2D phosphorene due to its anisotropic properties. The aim of this study is, therefore, to improve the efficiency of dye‐sensitized solar cells (DSSCs), considered to be the next generation of solar cells, by using 2D phosphorene material. To this end, a 2D phosphorene/black carbon hybrid material is prepared and used as a counterelectrode in DSSCs. This work also demonstrates the stability of the manufactured solar devices under different aging conditions. The results show that the device based on a 2D phosphorene/black carbon counterelectrode achieves an efficiency of 7.53%, compared with 5.68% for the pristine solar cell based on black carbon only. Interestingly, after 1200 h of continuous light exposure, the DSSC based on the hybrid 2D phosphorene/black carbon material retains 87% of its initial efficiency, while the pristine solar device maintains only 62.5% of its initial performance. This study paves the way for further research into 2D phosphorene material and its use in this promising solar technology.